Analysis of Gender Representation in the Film Luca (2021): A Critique of Hegemonic Masculinity - Al Firdaus, Juang Zuhdi; Khautsar, Daril Rakha; Saputra, Tegar Gunawan; Nirmalawati, Widya (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2025)
The animated film Luca (2021) contains many social messages related to how society views the role and identity of men. This study aims to analyze how forms of masculinity are represented in the film, particularly in relation to the concept of hegemonic masculinity. The method used is qualitative descriptive with a visual content analysis approach to key scenes in the film. Each scene analyzed was selected based on important moments that reveal the dynamics of male characters, whether through emotional expressions, inter character relationships, reactions to social pressure. The analysis results show that Luca presents a variety of masculinities, ranging from dominant and competitive to more emotionally open and accepting. The character Ercole, example, exemplifies aggressive and exclusive hegemonic masculinity, while Luca and Alberto demonstrate alternative forms of masculinity that are more reflective and emotional. The film also depicts the transformation of the main character from a fearful attitude to an individual who dares to express his identity, including in the context of friendship and future choices. This transformation reflects the potential for boys to move beyond traditional masculine expectations and explore more personal versions of themselves. The conclusion of this study affirms that masculinity in the film Luca is not presented in a singular manner but is diverse and open to interpretation as a critique of rigid gender norms. This study does not aim to generalize all forms of masculinity in animated films but only discusses the representations found in Luca based on the author's subjective analysis and interpretation.